Paraneoplastic cerebellar degeneration associated with anti-Yo antibodies in an ovarian cancer case: A case report - Sandra Deac; Mihaela Marioara Stana; Andrei Dan Havasi; Calin Cainap; Anca-Raluca Popita; Ana Maria Bordeianu; Simona Cainap; Madalina Bota; Ovidiu Vasile Bochis (Elsevier, 2021)
Paraneoplastic neurologic syndromes (PNS) are a rare heterogeneous group of disorders associated with malignancy that can result in significant functional impairment. One syndrome in particular, paraneoplastic cerebellar degeneration (PCD), may be severely disabling. PCD is a rare neurological syndrome, associated with active or subclinical cancer, characterized by acute or subacute onset cerebellar ataxia due to tumor-induced autoimmunity against cerebellar antigens. Treatment of paraneoplastic syndromes is generally unsatisfactory, but early diagnosis and treatment of PCD, which includes neurological treatment, immunotherapy and oncological treatment of associated malignancy, may improve the neurological prognosis. We reported the case of a 59-year-old woman who presented PCD as the first sign of ovarian cancer. Laboratory investigations showed the presence of anti-Yo antibodies in the serum. The brain MRI revealed specific modifications for PCD. After oncological treatment, intravenous immunoglobulin therapy and corticosteroid therapy, the oncological response was satisfactory, but no improvement of the neurologic symptoms was achieved.